2019
DOI: 10.1016/j.ophtha.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Durability of Voretigene Neparvovec-rzyl in RPE65 Mutation–Associated Inherited Retinal Dystrophy

Abstract: Purpose: To report the durability of voretigene neparvovec-rzyl (VN) adeno-associated viral vectorebased gene therapy for RPE65 mutationeassociated inherited retinal dystrophy (IRD), including results of a phase 1 follow-on study at year 4 and phase 3 study at year 2.Design: Open-label phase 1 follow-on clinical trial and open-label, randomized, controlled phase 3 clinical trial.Participants: Forty subjects who received 1.5Â10 11 vector genomes (vg) of VN per eye in at least 1 eye during the trials, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
216
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(231 citation statements)
references
References 23 publications
4
216
0
11
Order By: Relevance
“…In earlier phase I trials, improvements in vision following treatment were maintained through to the latest published follow-up time points (7.5 and 4 years), providing supporting evidence on the durability of the treatment effect [20,21].…”
Section: Clinical Trialsmentioning
confidence: 78%
“…In earlier phase I trials, improvements in vision following treatment were maintained through to the latest published follow-up time points (7.5 and 4 years), providing supporting evidence on the durability of the treatment effect [20,21].…”
Section: Clinical Trialsmentioning
confidence: 78%
“…This was subsequently expanded to include a milder, dominant form of retinopathy and more recently, to include less severe autosomal recessive retinopathies [35,37]. Luxturna, the first ocular gene therapy approved by the FDA, is for biallelic RPE65 retinal disease [16]. RPE65 c.1430A>G (p.Asp477Gly) remains the predominant RPE65 genotype observed in the Irish population.…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that aberrant RNA splicing has been shown to have a major pathogenic effect in a knock-in mouse model with this variant [71]. Given the success of the gene therapy treatment of biallelic RPE65 retinopathies with Luxturna [16], an AAV-based therapy, it is interesting to speculate whether the therapy might have any utility for monoallelic dominant RPE65 cases.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Some clinical trials of adeno-associated viral vector-based gene therapy for RPE65-related IRD have reported sustained visual improvements lasting up to at least 4 years after treatment. 24,25 However, other follow-up studies revealed that after 3 years, despite initial improvement in visual function, gene therapy failed to halt or even slow photoreceptor degeneration in these patients. [24][25][26][27][28][29] Three hypotheses have been proposed to explain why the results of gene supplementation during longterm follow up may be disappointing for these chronic conditions.…”
Section: Sustainability Of Therapy and Need For Retreatmentmentioning
confidence: 99%
“…24,25 However, other follow-up studies revealed that after 3 years, despite initial improvement in visual function, gene therapy failed to halt or even slow photoreceptor degeneration in these patients. [24][25][26][27][28][29] Three hypotheses have been proposed to explain why the results of gene supplementation during longterm follow up may be disappointing for these chronic conditions. First, expression of the delivered gene may have been too low in humans, perhaps as a result of poor transduction due to inefficient gene delivery and/or transcriptional silencing of the therapeutic transgene despite robust transduction.…”
Section: Sustainability Of Therapy and Need For Retreatmentmentioning
confidence: 99%